2016
DOI: 10.1016/j.jallcom.2016.04.218
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for design optimization of chemistry of hard magnetic alloys using experimental data

Abstract: A multi-dimensional random number generation algorithm was used to distribute chemical concentrations of each of the alloying elements in the candidate alloys as uniformly as possible while maintaining the prescribed bounds on the minimum and maximum allowable values for the concentration of each of the alloying elements. The generated candidate alloy compositions were then examined for phase equilibria and associated magnetic properties using a thermodynamic database in the desired temperature range. These in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…SOMs can be considered as a nonlinear generalization of principal component analysis (PCA), an unsupervised machine learning method [20,22]. Recent studies demonstrated the advantage of using SOM over PCA [10,14]. Most importantly, SOMs have been successfully used for feature extraction of scarce datasets (sample size of about 40), whereas conventional neural networks require very large training datasets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SOMs can be considered as a nonlinear generalization of principal component analysis (PCA), an unsupervised machine learning method [20,22]. Recent studies demonstrated the advantage of using SOM over PCA [10,14]. Most importantly, SOMs have been successfully used for feature extraction of scarce datasets (sample size of about 40), whereas conventional neural networks require very large training datasets.…”
Section: Methodsmentioning
confidence: 99%
“…SOMs can be considered as a nonlinear generalization of principal component analysis (PCA), an unsupervised machine learning method [20,22]. Recent studies demonstrated the advantage of using SOM over PCA [10,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coalbed methane is an important source of natural gas that is produced during coal formation and found in coal seams in an adsorbed state [1,2]. Coalbed methane is generally produced through drainage and pressure lowering [3]. In this process, coalbed methane-produced water is also produced.…”
Section: Introductionmentioning
confidence: 99%
“…Spinodal decomposition occurs during thermomagnetic treatment, and the temperature and time of this step have been studied to optimize the size and shape of the α1 phase formed [1,[3][4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%